Knowledge sharing in health Community of Practice (CoP) and Online Health Communities (OHCs): A bibliometric analysis - Muhammad Ashraf, Fauzi (World Scientific Publishing Co Pte Ltd, 2023)
This study aims to provide a scientific mapping based on a bibliographic database of knowledge sharing in the health community of practice (CoP) and online health communities (OHCs). These online platforms have provided an efficient means for members to share best practices, expertise, and information on health-related matters and acquire knowledge in the fast-moving health and medical field. Applying a bibliometric method, this study contributes to the body of knowledge concerning health CoP function, capacity, and contribution. This study tends to uncover past themes (citation analysis), current themes (co-citation analysis), and predict trends (co-word analysis) on health CoP and OHCs perspectives. Findings indicate the imperative role of CoP in the field, mainly due to the rapid development of sophisticated tacit knowledge on complicated health issues and unpredictable diseases affecting public health. Implications on theory and managerial aspect to strengthen the function of CoP in providing optimum health service to the public is discussed.